Insecticidal activity of Wild Spikenard (Hyptis suaveolens L. Poit) on Adult Mortality and Female Oviposition of Groundnut Bruchid, Caryedon serratus Olivier on stored Groundnut Seeds and Tamarind pods - I. Umar A. Mohammed, C. S. Oaya, A. M. Malgwi (Recent Research in Science and Technology, 2017)
An investigation was conducted to estimate the insecticidal deterrence of wild Spikenard (Hyptis suaveolens L. Poit) on adult mortality and female oviposition of groundnut bruchid, Caryedon serratus Olivier on stored groundnut seeds and tamarind pods. Data were taken on mean percentage mortality and mean number of eggs laid (female oviposition). The highest mean percentage mortality for both stored produces were reported in actellic dust and 12.00g levels of H. suaveolens whole powders (93.50; 91.75 and 92.25; 91.25) while the least were obtained in the controls (4.75; 3.25). Moreover, 12.00g levels of H. suaveolens whole powder and actellic dust recorded the least mean number of eggs laid (female oviposition) (18.00; 17.00 and 19.25; 18.00) while the highest was reported in the controls (318.25; 305.50) respectively. There was no significant difference between the effects of rates of synthetic insecticides and 12.00g level of H. suaveolens whole powder in all the parameters measured.